Book Review: Moral Economic Transitions in the Mongolian Borderlands - Myadar, Orhon (Studies of Transition States and Societies, 2025)
Moral Economic Transitions in the Mongolian Borderlands: A Proportional Share by Hedwig Amelia Waters, 2023, UCL Press.